TAXBEN: the IFS microsimulation tax and benefit model - Chris Giles; Julian McCrae (Institute for Fiscal Studies (IFS), 1995)
A tax and benefit model is a computer program that calculates the effects of possible changes in the fiscal system on a sample of households. By using a sample which is representative of the population, such models allow users to make accurate inferences about the aggregate revenue implications of specific changes, and to examine the distributional effects of policy on different sub-groups of the population. Correspondingly, tax and benefit models play an important part in the analysis of fiscal policy in the UK and abroad. The IFS has operated a tax and benefit model of the UK, known as TAXBEN, since 1983. TAXBEN operates on data taken from the Family Expenditure Survey (FES), a yearly representative sample of 7,000 UK households. It was substantially revised in 1990, (see Johnson, Stark and Webb, 1990) and since then a range of extra features have been added which have significantly enhanced TAXBEN's power as a tool for the analysis of policy. These include new routines modelling individual's budget constraints and replacement rates which, together with closer compatibility with the IFS labour supply model, Simulation Package for the Analysis of Incentives (SPAIN, Duncan,1991), have allowed us to use TAXBEN to examine behavioural responses to policy changes. The purpose of this working paper is to document the current TAXBEN model, given the changes that have occurred since 1990.
Keywords: 330